Regioselective nitration of anilines with Fe(NO3)3·9H2O as a promoter and a nitro source. Issue 21 (10th May 2018) - Gao, Yang; Mao, Yuanyou; Zhang, Biwei; Zhan, Yingying; Huo, Yanping
Abstract : A novel and efficient ortho -nitration reaction of aniline derivatives using the inexpensive and nontoxic Fe(NO3 )3 ·9H2 O as a promoter and a nitro source has been developed. Abstract : An efficient Fe(NO3 )3 ·9H2 O promoted ortho -nitration reaction of aniline derivatives has been developed. This reaction may go through a nitrogen dioxide radical (NO2 ˙) intermediate, which is generated by the thermal decomposition of iron(iii ) nitrate. The practicality of the present method using nontoxic and inexpensive iron reagents has been shown by the broad substrate scope and applications.